Records Committee review for rare bird sighting for Eskimo Curlew at Northwestern Iowa in 1866 - Iowa Ornithologists' Union Records Committeeet al (1901)
Records Committee review for Eskimo Curlews in Northwestern Iowa in the spring of 1866. Includes a record review document with votes and the original sighting record found in the publication The dough bird again in Forest and Stream 56:146 by E. Hough seen by John Smith. Epson - sheet feed